Variation of Temperature Responses Resulting from HIFU Application According to Acoustic Parameters [HIFU Uygulamasi Sonucu Oluşan Sicaklik Yanitinin Akustik Parametrelere Göre Deǧişimi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
In recent years, High Intensity Focused Ultrasound (HIFU) has been actively used in clinical practice for the treatment of some certain types of cancer. However, as in other cancer treatment methods, dosimetric studies have to be carried out in order to achieve effective treatment. For HIFU applications, dosimetric studies are performed as temperature characterizations on tissue mimicking materials (TMM) that simulate the acoustic properties of the selected tissues. However, due to the acoustical properties of each tissue are different, it is thought that it would give more accurate results by using TMMs which has equivalent acoustic parameters of related tissue while performing temperature characterizations. In this study, the temperature changes resulting from the application of HIFU were determined on two different TMM, which are produced from Agar and Phytagel and have different acoustic parameters, by using thermocouples embedded in TMM. In this manner, temperature values were measured under identical conditions except from acoustical parameters and it was tried to show the dependence of temperature on acoustical parameters. © 2018 IEEE.
Keywords: acoustic parameters; cancer; HIFU; temperature increase; thermocouple; tissue mimicking material